UL36 Rescues Apoptosis Inhibition and In vivo Replication of a Chimeric MCMV Lacking the M36 Gene - Chaudhry, M. Zeeshan; Kasmapour, Bahram; Plaza-Sirvent, Carlos; Bajagic, Milica; Casalegno Garduño, Rosaely; Borkner, Lisa; Lenac Roviš, Tihana; Scrima, Andrea; Jonjic, Stipan; Schmitz, Ingo; Cicin-Sain, Luka (Frontiers in Cellular and Infection Microbiology, 2017)
Apoptosis is an important defense mechanism mounted by the immune system to control virus replication. Hence, cytomegaloviruses (CMV) evolved and acquired numerous anti-apoptotic genes. The product of the human CMV (HCMV) UL36 gene, pUL36 (also known as vICA), binds to pro-caspase-8, thus inhibiting death-receptor apoptosis and enabling viral replication in differentiated THP-1 cells. In vivo studies of the function of HCMV genes are severely limited due to the strict host specificity of cytomegaloviruses, but CMV orthologues that co-evolved with other species allow the experimental study of CMV biology in vivo. The mouse CMV (MCMV) homolog of the UL36 gene is called M36, and its protein product (pM36) is a functional homolog of vICA that binds to murine caspase-8 and inhibits its activation. M36-deficient MCMV is severely growth impaired in macrophages and in vivo. Here we show that pUL36 binds to the murine pro-caspase-8, and that UL36 expression inhibits death-receptor apoptosis in murine cells and can replace M36 to allow MCMV growth in vitro and in vivo. We generated a chimeric MCMV expressing the UL36 ORF sequence instead of the M36 one. The newly generated MCMVUL36 inhibited apoptosis in macrophage lines RAW 264.7, J774A.1, and IC-21 and its growth was rescued to wild type levels. Similarly, growth was rescued in vivo in the liver and spleen, but only partially in the salivary glands of BALB/c and C57BL/6 mice. In conclusion, we determined that an immune-evasive HCMV gene is conserved enough to functionally replace its MCMV counterpart and thus allow its study in an in vivo setting. As UL36 and M36 proteins engage the same molecular host target, our newly developed model can facilitate studies of anti-viral compounds targeting pUL36 in vivo.